Optimization temperature and Boron modulate Phytohormnes content to improve fruit set for Barhee date palm (Phoenix dactylifera L.) cultivar derived from tissue culture - Shareef, Hussein J. (Basrah Journal Of Date Palm Research, 2024)
Temperature is one of the crucial factors that can affect the success of pollination in date palm. The present investigated the impact of bagging treatments and boron spraying on temperature, hormone levels, and fruit set in Barhee date palms cultivar derived from tissue culture. The study also measured the levels of plant hormones, including indole acetic acid, gerbilline acid, kinetin-like compound, and abscisic acid, before and after pollination under different treatments. The results showed that bagging treatments significantly affected the temperature inside the bags, with higher temperatures observed in the white paper treatment. The results also showed that the levels of these hormones varied depending on the treatment and stage of fruit development. the high levels of IAA and KC show in the pollination treatments involving brown paper and white paper, the highest levels of GA3 were found in bagging with brown paper without pollination. The temperature has been shown to significantly affect the levels of GAs and ABA in flowers, leading to Parthenocarpic fruit. Treatment with spraying boron and bagging with brown paper showed the highest percentage of seeded fruit set while bagging with brown paper without pollination resulted in the highest percentage of seedless fruit set. The study highlights the importance of carefully managing bagging treatments for successful pollination and fruit set in date palm cultivation. Maintaining optimal temperature conditions is crucial for successful pollination in date palms.